2017
DOI: 10.1016/j.cplett.2017.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic, electrochemical and thermoelectric properties of P2-Nax(Co7/8

Abstract: We theoretically investigated the electronic, electrochemical and magnetic properties of Sb doped Na x CoO 2 (x = 1, 0.75 and 0.50). Sb Co dopants adopt +5 oxidation state in Na x CoO 2 host lattice for all Na concentrations (x). Due to high oxidation states, Sb 5+ strongly repels Na ions and therefore it decreases the electrochemical potential (vs. Na/Na + ). The electrons introduced by Sb 5+ localize on nearby Co ions creating Co 2+ species which are absent in undoped Na x CoO 2 . Co 2+ ions reduce the spin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…The main findings of this investigation can be summarised as follow: (1) Sb Co is the most stable configuration Na 0.875 CoO 2 as it is in Na 1 CoO 2 as well. This trend is similar to the Sb dopant in other sodium cobaltates with smaller Na concentrations [26,27]. Moreover, as x increases the margin of the stabilisation of Sb Co configuration increases against those other configurations in which Sb is located in the Na layer; (2) the formation energy of Sb Co decreases with decreasing x-E f (Na 1 CoO 2 :Sb Co ) = 1.356 eV and E f-(Na 0.875 CoO 2 :Sb Co ) = 1.175 eV.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The main findings of this investigation can be summarised as follow: (1) Sb Co is the most stable configuration Na 0.875 CoO 2 as it is in Na 1 CoO 2 as well. This trend is similar to the Sb dopant in other sodium cobaltates with smaller Na concentrations [26,27]. Moreover, as x increases the margin of the stabilisation of Sb Co configuration increases against those other configurations in which Sb is located in the Na layer; (2) the formation energy of Sb Co decreases with decreasing x-E f (Na 1 CoO 2 :Sb Co ) = 1.356 eV and E f-(Na 0.875 CoO 2 :Sb Co ) = 1.175 eV.…”
Section: Discussionsupporting
confidence: 76%
“…This is in contrast to the pristine Na 0.875 CoO 2 compounds in which the Co 4+ ions were antiferromagnetically aligned across the CoO 2 planes [56,57]. Moreover, we have earlier shown that in Na 1 CoO 2 and Na 0.75 CoO 2 , Sb Co dopant also adopts the higher oxidation state [27].…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Computational screening has recently emerged as a novel tool in the discovery of brand-new thermoelectric materials. [25][26][27][28][29][30] Subsequently, through computational survey into uncharted materials' territory, one may find a desirable oxide alternative to the common thermoelectric materials, at least for those applications where exposure to elements is inevitable. More specifically, our study was motivated by the recent prediction, 31 and observation 32 of spinel oxides with high Seebeck coefficient, and high-performance thermoelectric cubic oxides.…”
Section: Introductionmentioning
confidence: 99%